2013
DOI: 10.1155/2013/670130
|View full text |Cite
|
Sign up to set email alerts
|

Singlet Generation from Triplet Excitons in Fluorescent Organic Light-Emitting Diodes

Abstract: A potential major drawback with organic light-emitting devices, (OLEDs) is the limit of 25% singlet exciton production through spin-dependent charge recombination. Recent device results, however, show that this limit does not hold and far higher efficiencies can be achieved in purely fluorescent-based systems (Wohlgenannt et al. (2012)). Here, the various routes by which triplet excitons can generate singlet states are discussed and their relative contributions to the overall electroluminescence yield are giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 148 publications
(199 reference statements)
1
55
0
Order By: Relevance
“…It was also shown that approximately 20% of the device efficiency originated from the production of singlet excitons by TTA in the fluorescent conjugated polymer OLED using F8-PFB and an interlayer of F8-TFB [41]. A similar phenomenon was observed in a polymer OLED with a spirofluorene derivative [42]. This mechanism yielded a very high emission efficiency of 10% EQE with y = 0.13 in a blue-emitting device [43].…”
Section: Polymer Oledmentioning
confidence: 88%
“…It was also shown that approximately 20% of the device efficiency originated from the production of singlet excitons by TTA in the fluorescent conjugated polymer OLED using F8-PFB and an interlayer of F8-TFB [41]. A similar phenomenon was observed in a polymer OLED with a spirofluorene derivative [42]. This mechanism yielded a very high emission efficiency of 10% EQE with y = 0.13 in a blue-emitting device [43].…”
Section: Polymer Oledmentioning
confidence: 88%
“…It was also shown that approximately 20% of the device efficiency originated from the production of singlet excitons by TTA in the fluorescent conjugated polymer OLED using F8-PFB and an interlayer of F8-TFB [5]. A similar phenomenon was observed in a polymer OLED with a spiro-fluorene derivative [6]. This mechanism yielded a very high emission efficiency of 10% EQE with y = 0.13 in a blue-emitting device [7].…”
Section: Singlet Yield From Unique Tta Systemmentioning
confidence: 62%
“…We have seen that a small ΔE ST can be obtained by replacing the central Si atom of the substituent with a C atom, which leads to a low radiative decay rate according to Fermi's golden rule [46]. Overall, the molecules which the central atom is Si has a suitable ΔE ST .…”
Section: Singlet Versus Triplet Energymentioning
confidence: 95%